MENINGKATKAN KEAKTIFAN SISWA PADA MATERI PENGUKURAN PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL PBL DI KELAS V SDN 186/I SRIDADI - Aisyah, Siti; Destrinelli; Isnania (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ learning activeness in mathematics measurement material through the implementation of the Problem Based Learning (PBL) model in Grade V of SDN 186/I Sridadi. This research employed Classroom Action Research (CAR) using both qualitative and quantitative approaches. Data were collected through observation, interviews, and documentation techniques. The study adopted the Kemmis and McTaggart model consisting of four stages: planning, implementation, observation, and reflection. The results indicated that the implementation of the PBL model was effective in improving students’ learning activeness. This improvement was reflected in the increasing percentage of students’ activeness from one cycle to the next. Initially, students’ activeness in Cycle I was categorized as low, reaching 47.36%. In Cycle II, the first meeting showed an increase to 76.47%, and further improvement occurred in the second meeting, reaching 83.33%. The percentage of students’ activeness exceeded the success indicator of 70%, indicating that the learning objectives had been achieved. Therefore, the action cycle was terminated after achieving the predetermined targets. The findings demonstrate that the application of the Problem Based Learning model significantly enhances students’ learning activities and activeness in mathematics learning. It can be concluded that the implementation of Problem Based Learning in mathematics instruction effectively improves the learning activeness of Grade V students.